Application of Amorphous Zirconium-Yttrium-Aluminum-Magnesium-Oxide Thin Film with a High Relative Dielectric Constant Prepared by Spin-Coating - Huiyun Yang; Zhihao Liang; Xiao Fu; Zhuohui Xu; Honglong Ning; Xianzhe Liu; Jiajing Lin; Yaru Pan; Rihui Yao; Junbiao Peng (Membranes, 2021)
Amorphous metal oxide has been a popular choice for thin film material in recent years due to its high uniformity. The dielectric layer is one of the core materials of the thin film transistor (TFT), and it affects the ability of charges storage in TFT. There is a conflict between a high relative dielectric constant and a wide band gap, so we solved this problem by using multiple metals to increase the entropy of the system. In this paper, we prepared zirconium-yttrium-aluminum-magnesium-oxide (ZYAMO) dielectric layers with a high relative dielectric constant using the solution method. The basic properties of ZYAMO films were measured by an atomic force microscope (AFM), an ultraviolet-visible spectrophotometer (UV-VIS), etc. It was observed that ZYAMO thin films had a larger optical band when the annealing temperature increased. Then, metal-insulator-metal (MIM) devices were fabricated to measure the electrical properties. We found that the leakage current density of the device is relatively lower and the ZYAMO thin film had a higher relative dielectric constant as the concentration went up. Finally, it reached a high relative dielectric constant of 56.09, while the leakage current density was no higher than 1.63 × 10−6 A/cm2@ 0.5 MV/cm at 1.0 M and 400 °C. Therefore, the amorphous ZYAMO thin films has a great application in the field of high permittivity request devices in the future.